Lietuvių veiksmažodžio morfologijos įsisavinimo klausimu - Wójcik, Paweł (Kalbotyra, 1997)
The paper presents some results of a study on the acquisition of Lithuanian verb morphology based on the analysis of tape-recorded data of a Lithuanian girl, named Rūta, from the age of 1;7 to 2;6. The recordings were made on a free basis, without a fixed schedule. They were put into a computer file format double checked for accuracy and coded in accordance with CHILDES (McWhinney, Snow, 1990). In the girl’s utterances 9667 identifiable verb forms were singled out. In adult input to Rūta 16730 verb were coded. The frequency data show that there is a close match between the distribution of stem types and lexeme types in Rūta and in input (fig. 1.1 & 1.2). At the beginning of the period studied the number of stem types and tokens is relatively small both in child’s and parents’ utterances. During the following months this number increases, and so does the ratio of the number of stem tokens to the number of lexeme tokens. The distribution of particular morphological categories in child and input (tab. 3.1 and 3.2) is generally very similar. There are but few differences pertaining to pragmatics (imperative, impersonal predicate galima), or resulting from the use of more complicated syntactic constructions by adults (conditional and infinitive). Similarities can also be observed in the distribution of the category of person in Rūta’s utterances and those of adults. The most frequent is the 3rd p., which is very often used (both by the girl and adults) in self-reference and in addressing others. The opposite ratio of 1 sg to 2 sg forms is motivated by the situational context - since the girl is more often the topic of the conversation than the person the girl interacts with, there are more 1 sg than 2 sg forms in the Rūta’s utterances, and in the input 2 sg is more frequent than 1 sg. In the paper, the most frequent errors connected with the acquisition of person are presented and discussed. The data show that most of the verb stems and verb tokens both in the child and in the input belong to the 1st conjugation. Therefore one can expect over regularization of the 2nd and 3rd conjugation verbs. However, the only observed clear example of the regularization and shifts (spotted mostly in the earlier months of the period studied) is replacement of the ending -i, which marks 3rd person of 2nd conjugation verbs, with the 1st conjugation ending -(i)a: *mylia for myli, *tuja for turi, *gulia for guli, etc. The 3rd conjugation verbs are not shifted, which means that the stem/token frequency is not a sufficient condition for regularization, and that there must be an additional trigger within the verb class itself to condition a shift. In case of the 2nd conjugation, the trigger is the formal resemblance of 1st and 2nd conjugation paradigms. Next, some problems pertaining to affixation are discussed: Erroneous prefixation, e.g.: omission of a prefix: *Ø-tetyti for ati-daryti; marking the prefix with a filler (neutral vowel a or reduplicated syllable): *a-tetyti for atidaryti, *de-dėti for pa-dėti. Erroneous usage of reflexives, e.g.: omission of the particle -si(-): *ne-Ø-kelk for ne-si-kelk; marking the particle with a filler (reduplicated syllable): *akikėlė (for atsikėlė); leaving the particle at the and of the word while using a prefixed form: *ne-tiupa-s for ne-si-supa. Some further errors were pointed out without being analysed in detail.